EFEKTIVITAS PENINGKATAN KEMAMPUAN MENGINGAT KOSAKATA BAHASA JEPANG MENGGUNAKAN PERMAINAN SHIRITORI - Igat Meliana; Kliwon Sahudi; Nisa Indra Syalina (Jurnal Sora : Pernik Studi Bahasa Asing, 2022)
This study discusses the shiritori game in learning Japanese vocabulary for students of Persada Bhakti Junior High School Bekasi. The purpose of this study was to determine the increase in student learning scores using the shiritori game. The object of this research is the eighth grade students of SMP Persada Bhakti Bekasi. This research is a pre-experimental research which is characterized by the absence of a comparison group. The design used in this study was a one group pretest-posttest design. The method of data collection is in the form of test questions in the form of 10 multiple choice questions and 7 essay questions. The average pretest score is 43 while the posttest score is 78.7. So the result of this research is that there is a significant effect on the level of mastery of Japanese vocabulary using the shiritori game method. So, it can be concluded that the shiritori game is effective in increasing the Japanese vocabulary skills of eighth grade students of SMP Persada Bhakti Bekasi.